2022
DOI: 10.1093/jxb/erac239
|View full text |Cite
|
Sign up to set email alerts
|

Functions and mechanisms of the Ubc13-UEV complex and lysine 63-linked polyubiquitination in plants

Abstract: Ubiquitination is one of the best-known post-translational modifications in eukaryotes, in which different linkage types of polyubiquitination result in different outputs of the target proteins. Distinct from the well-characterized K48-linked polyubiquitination that usually serves as a signal for degradation of the target protein, K63-linked polyubiquitination often requires a unique E2 heterodimer Ubc13-UEV and alters the target protein activity instead of marking it for degradation. This review focuses on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 171 publications
0
2
0
Order By: Relevance
“…Subsequent studies reveal that AtUBC13 s function in apical dominance [ 23 ], DDR [ 22 ], iron metabolism [ 24 ], auxin signaling [ 25 ], low temperature stress response [ 26 ] and plant immunity [ 26 , 27 ]. In addition, systematic studies in Arabidopsis revealed additional target proteins modified by K63-linked polyubiquitination [ 28 , 29 ], indicating that plant Ubc13s play multiple roles in plant development and stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies reveal that AtUBC13 s function in apical dominance [ 23 ], DDR [ 22 ], iron metabolism [ 24 ], auxin signaling [ 25 ], low temperature stress response [ 26 ] and plant immunity [ 26 , 27 ]. In addition, systematic studies in Arabidopsis revealed additional target proteins modified by K63-linked polyubiquitination [ 28 , 29 ], indicating that plant Ubc13s play multiple roles in plant development and stress responses.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Single ubiquitin molecules have seven surface Lys residues (K6, K11, K27, K29, K33, K48, and K63), and ubiquitin molecules can be sequentially added to one of their own Lys residues, known as polyubiquitination. 15 Various types of chains play different roles in different cellular processes, the most widely studied of which are K48, K63, and linear ubiquitin chains. As TRIM55 is an E3 ubiquitin ligase, the specific mechanism of ubiquitination is unknown.…”
Section: Introductionmentioning
confidence: 99%